2022
DOI: 10.2991/aebmr.k.220307.012
|View full text |Cite
|
Sign up to set email alerts
|

Application and Comparison of NPV and IRR Methods in the Company Investment Decision

Abstract: In order to find out the application conditions of Net Present Value (NPV) and Internal Rate of Return (IRR) in practice, based on previous studies, the paper summarized the advantages and disadvantages of the two methods and explores the specific application conditions in corporate finance. The results showed that the NPV method can reflect the liquidity and overall profitability of investment, provide clear expectations, and be more comprehensive in risk measurement. However, the NPV method could not avoid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The IRR and NPV methods are widely used by investors, project planners, and researchers to evaluate the financial viability of investment projects. According to Huang et al [99], the IRR is a practical method that allows calculating the economic profitability of the invested capital, and the ratio forms simplify the comparison of projects. Regarding the NPV, the authors argued that it offers four advantages: (i) it considers the value of money through time; (ii) it is calculated from the cashflows discounted from the project, which includes the income and outcome; (iii) it includes risk assessments based on the discount ratio used to calculate the actual cashflow value; and (iv) the acceptance or rejection criterion is simple so that it facilitates decision-making processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRR and NPV methods are widely used by investors, project planners, and researchers to evaluate the financial viability of investment projects. According to Huang et al [99], the IRR is a practical method that allows calculating the economic profitability of the invested capital, and the ratio forms simplify the comparison of projects. Regarding the NPV, the authors argued that it offers four advantages: (i) it considers the value of money through time; (ii) it is calculated from the cashflows discounted from the project, which includes the income and outcome; (iii) it includes risk assessments based on the discount ratio used to calculate the actual cashflow value; and (iv) the acceptance or rejection criterion is simple so that it facilitates decision-making processes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to that, the use of deterministic methods to evaluate investment projects, such as the discounted cashflow (on which the IRR and NPV are based), may lead to inappropriate decisions because they do not consider changes in cash flows associated with project uncertainty; they assume that the rate at which cash flows are reinvested does not vary and that investors keep their expectations of profitability and investment alternatives constant. In this sense, Huang et al [99] also stated that the cashflows' variability is a disadvantage of the traditional methods, and they add other drawbacks such as the selection of discount ratios (which should consider the systematic and non-systematic risk of the investment project), the NPV's sensitivity, and the investment decision-making's static nature of these methods. Regarding the latter, Andreolli et al [94] agreed with the fact that the NPV assesses the projects at a moment in time, but it does not consider the possibility of reacting against the changes in external and internal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold rate chosen in the study is the discount rate applied, as reported in the CBA Guide to Investment Projects [41]. Unlike the NPV, the IRR is a dimensionless indicator; that is, it is not affected by the size of the investment [41,44]. This is an important aspect for a performance indicator, as the dimensionality of the index could lead to larger projects being accepted over smaller investments.…”
Section: Cost-benefit Analisys (Cba)mentioning
confidence: 99%
“…In the actual investment process, as long as the expected cash flow is reached, the final IRR will be determined. The disadvantage of the IRR indicator is that when there are multiple options for investment schemes, due to the calculation method of IRR, multiple results may be generated, and there may be multiple IRRs, or there may be no results [4]. Therefore, the indicator analysis of mutually exclusive financial investment projects may mislead investors.…”
Section: Comparative Analysis Of Advantages and Disadvantages Of Npv ...mentioning
confidence: 99%